2021
DOI: 10.3390/md19020050
|View full text |Cite
|
Sign up to set email alerts
|

Design and Preclinical Evaluation of Chitosan/Kaolin Nanocomposites with Enhanced Hemostatic Efficiency

Abstract: In the current study, hemostatic compositions including a combination of chitosan and kaolin have been developed. Chitosan is a marine polysaccharide derived from chitins, a structural component in the shells of crustaceans. Both chitosan and kaolin have the ability to mediate a quick and efficient hemostatic effect following immediate application to injury sites, and thus they have been widely exploited in manufacturing of hemostatic composites. By combining more than one hemostatic agent (i.e., chitosan and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The method to coat the cotton gauze in a heated kaolin solution is conventionally used 26,27 . However, one study result shows that direct coating of kaolin slurry results in low coating efficiency and gives relatively low hemostatic efficiency 28 . To achieve higher hemostatic efficiency and lesser detachment of kaolin from the dressing the Kaolin solution is gradually added to the chitosan solution with continuous heating and stirring the solution.…”
Section: Materials and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The method to coat the cotton gauze in a heated kaolin solution is conventionally used 26,27 . However, one study result shows that direct coating of kaolin slurry results in low coating efficiency and gives relatively low hemostatic efficiency 28 . To achieve higher hemostatic efficiency and lesser detachment of kaolin from the dressing the Kaolin solution is gradually added to the chitosan solution with continuous heating and stirring the solution.…”
Section: Materials and Methodologymentioning
confidence: 99%
“…Kaolin rapidly promotes blood coagulation by activating the factor XII protein which initiates the coagulation cascade 30,31 . In a previous study, it has been analyzed that the kaolin/chitosan composites showed significantly reduced clotting time and enhanced hemostatic efficiency 28 calculated in two rats after puncturing their leg vein and reapplying hemostatic dressing every 10 seconds until the time when the bleeding stopped. In all the models the respective dressings were applied immediately after the injury with immediate compression.…”
Section: 11) In Vitro Hemostatic Efficiency In Ratsmentioning
confidence: 99%
“…These nanocomposite materials are gaining importance due to their excellent biocompatible properties and not introducing any clinical or biochemical changes after their applications. Studies proved that combining more than one hemostatic agent such as kaolin-chitosan composite have improved the efficiency of bleeding control [22]. This could be due to the increased surface area and multiple components responsible for more than one mechanism in treating wounds.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Interestingly, the mechanical resistance and stability of CS derivatives can be significantly improved by their non-covalent association to specific additives. This strategy was highlighted in bone tissue engineering and wound dressing applications [ 101 , 102 ] and is also suitable for the development of pH-responsive conjugates [ 103 ]. This section describes systems involving non-functionalized CS forming non-covalent interactions with other components including polymers, proteins, small molecules, and nanocomposites.…”
Section: Non-covalent Modificationsmentioning
confidence: 99%
“…SEM can give essential insights into structure porosity, pore size, and roughness degree of hydrogels, nano/micro-fibers, and NPs based on CS [ 31 , 43 ]. The roughness degree is particularly important in applications such as wound healing, where cell attachment and proliferation has to be favored [ 82 , 102 ], or in food packaging, where smooth surfaces are preferred [ 50 ]. SEM is also a method of choice to observe and measure the pores of CS composites and molecular organic framework (MOF) [ 130 , 175 ].…”
Section: Characterization Of Cs-based Materialsmentioning
confidence: 99%